Mediterranean water resources in a global change scenario - García-Ruiz, José M.; López-Moreno, J. Ignacio; Vicente-Serrano, Sergio M.; Lasanta–Martínez, Teodoro; Beguería, Santiago (Earth-science reviews, 2011)
Mediterranean areas of both southern Europe and North Africa are subject to dramatic changes that will affect the sustainability, quantity, quality, and management of water resources. Most climate models forecast an increase in temperature and a decrease in precipitation at the end of the 21st century. This will enhance stress on natural forests and shrubs, and will result in more water consumption, evapotranspiration, and probably interception, which will affect the surface water balance and the partitioning of precipitation between evapotranspiration, runoff, and groundwater flow. As a consequence, soil water content will decline, saturation conditions will be increasingly rare and restricted to periods in winter and spring, and snow accumulation and melting will change, especially in the mid-mountain areas. Future land management will be characterized by forest and shrub expansion in most Mediterranean mountain areas, as a consequence of farmland and grazing abandonment, with increasing human pressure localized only in some places (ski resort and urbanized of valley floors). In the lowlands, particularly in the coastal fringe, increasing water demand will occur as a consequence of expansion of irrigated lands, as well as the growth of urban and industrial areas, and tourist resorts. Future scenarios for water resources in the Mediterranean region suggest (1) a progressive decline in the average streamflow (already observed in many rivers since the 1980s), including a decline in the frequency and magnitude of the most frequent floods due to the expansion of forests; (2) changes in important river regime characteristics, including an earlier decline in high flows from snowmelt in spring, an intensification of low flows in summer, and more irregular discharges in winter; (3) changes in reservoir inputs and management, including lower available discharges from dams to meet the water demand from irrigated and urban areas. Most reservoirs in mountain areas will be subject to increasing water resource uncertainty, because of the reduced influence of snow accumulation and snowmelt processes. Besides, reservoir capacity is naturally reduced due to increasing sedimentation and, in some cases, is also decreased to improve the safety control of floods, leading to a reduction in efficiency for agriculture. And (4) hydrological and population changes in coastal areas, particularly in the delta zones, affected by water depletion, groundwater reduction and saline water intrusion. These scenarios enhance the necessity of improving water management, water prizing and water recycling policies, in order to ensure water supply and to reduce tensions among regions and countries.